EVALUATION OF THE EFFECTIVENESS OF VILLAGE FINANCIAL MANAGEMENT IN IMPROVING COMMUNITY WELFARE - Febrianto, Farid; Wijayantini, Bayu; Setianingsih, Wahyu Eko (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This research aims to find out whether village financial management in Wringin Agung Village, Jombang District, Jember Regency is effective. This type of research is quantitative descriptive. The sample used in this research is the financial report on the allocation of village funds in the village income and expenditure budget at the Wringin Agung Village office, Jember Regency from 2018 to 2022. The results of this research show that the average 5-year effectiveness ratio is 76% up to 101% indicates that the ratio is effective, the income and expenditure growth ratio over 5 years averages -19% to 22% indicating that the growth ratio is positive, for the criteria for the independence ratio of Wringin Agung Village over 5 years the average is 0%- 33% indicates that the independence ratio is very low, and for the Efficiency Ratio over 5 years the average is 88% - 97% indicating that the ratio is inefficient.